2016
DOI: 10.1002/jbmr.2854
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Migration Inhibitory Factor (MIF) Supports Homing of Osteoclast Precursors to Peripheral Osteolytic Lesions

Abstract: By binding to its chemokine receptor CXCR4 on osteoclast precursor cells (OCPs), it is well known that stromal cell-derived factor-1 (SDF-1) promotes the chemotactic recruitment of circulating OCPs to the homeostatic bone remodeling site. However, the engagement of circulating OCPs in pathogenic bone resorption remains to be elucidated. The present study investigated a possible chemoattractant role of macrophage migration inhibitory factor (MIF), another ligand for C-X-C chemokine receptor type 4 (CXCR4), in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 63 publications
3
39
0
Order By: Relevance
“…However, because OC-STAMP-KO mice show no bone phenotype, the present study was predicated on the hypothesis that OC-STAMP must be engaged in pathogenic bone resorption in periodontitis. On the other hand, we reported that OCps in circulation are recruited to the wear debris-induced bone lytic lesion through a unique chemokine, macrophage migration inhibitory factor (MIF), locally produced in the lesion (23), as opposed to stromal-derived factor 1 (SDF-1), which chemoattracts OCps in circulation to the healthy bone remodeling site (49). This study revealed that migration of CXCR4 + OCps in the circulation to either normal bone remodeling or pathogenic bone resorption sites is controlled by 2 different chemokines, MIF or SDF-1, respectively, suggesting that MIF mediates the recruitment of OCps toward pathogenic bone resorption lesion, whereas SDF-1 is engaged in the recruitment of OCps to the healthy homeostatic bone remodeling site (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because OC-STAMP-KO mice show no bone phenotype, the present study was predicated on the hypothesis that OC-STAMP must be engaged in pathogenic bone resorption in periodontitis. On the other hand, we reported that OCps in circulation are recruited to the wear debris-induced bone lytic lesion through a unique chemokine, macrophage migration inhibitory factor (MIF), locally produced in the lesion (23), as opposed to stromal-derived factor 1 (SDF-1), which chemoattracts OCps in circulation to the healthy bone remodeling site (49). This study revealed that migration of CXCR4 + OCps in the circulation to either normal bone remodeling or pathogenic bone resorption sites is controlled by 2 different chemokines, MIF or SDF-1, respectively, suggesting that MIF mediates the recruitment of OCps toward pathogenic bone resorption lesion, whereas SDF-1 is engaged in the recruitment of OCps to the healthy homeostatic bone remodeling site (23).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we reported that OCps in circulation are recruited to the wear debris-induced bone lytic lesion through a unique chemokine, macrophage migration inhibitory factor (MIF), locally produced in the lesion (23), as opposed to stromal-derived factor 1 (SDF-1), which chemoattracts OCps in circulation to the healthy bone remodeling site (49). This study revealed that migration of CXCR4 + OCps in the circulation to either normal bone remodeling or pathogenic bone resorption sites is controlled by 2 different chemokines, MIF or SDF-1, respectively, suggesting that MIF mediates the recruitment of OCps toward pathogenic bone resorption lesion, whereas SDF-1 is engaged in the recruitment of OCps to the healthy homeostatic bone remodeling site (23). To our knowledge, OC-STAMP appears to be the OC fusionregulatory molecule that is distinctively engaged in pathogenic bone resorption in periodontitis but not in homeostatic bone remodeling, which stands in contrast to DC-STAMP, which is engaged in both homeostatic and pathogenic bone remodeling by increasing cell fusion in a manner independent of OC-STAMP/CD9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially it has become evident that OCps in the circulation migrate to intact bone as well as inflammatory bone resorption lesion and participate in bone resorption [57,58], suggesting that OCps function similar to innate immune macrophages [59]. For this reason, it is plausible that any pharmaceutical intervention for bone lytic diseases that targets osteoclast differentiation, such as bisphosphonate and Denosumab [60,61], would attenuate the OCps-mediated anti-bacterial barrier mechanism for alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of PGDHC on in vivo osteoclastogenesis, a mouse model of calvarial injection was utilized following a published protocol with some modifications [30]. Under anesthesia with ketamine (80 mg/kg) and xylazine (10 mg/kg), WT or TLR2/4 DKO mice (6- to 8-week-old; 5 mice/group) received a calvarial injection of the following solutions: 1) 0.1% ethanol in PBS (control); 2) 10 μg/ml of murine recombinant RANKL (rRANKL) dissolved in PBS containing 0.1% ethanol; 3) a mixture of 10 μg/ml of murine rRANKL and 10 μg/ml of PGDHC dissolved in PBS containing 0.1% ethanol.…”
Section: Methodsmentioning
confidence: 99%